PENGEMBANGAN INVENTORI WELLNESS EVALUATION OF LIFESTYLE (WEL) UNTUK REMAJA - Rohmatus Isnaini; Ika Ayuningtyas; Arif Suhendarto (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
The objective of the research is to produce a Wellness Evaluation of Lifestyle(WEL) inventory for teenagers. The method is research and development by adaptingthe existing Wellness Evaluation of Lifestyle. The subjects of the research are 56students of State Junior High School 9 Yogyakarta and State Senior High School 4Yogyakarta. This reseacrh produces a Wellness Evaluation of Lifestyle (WEL) whichmeets the cultural condition, character, religion, and bahasa Indonesia. In the items ofthe Wellness Evaluation of Lifestyle (WEL) inventori there are 17 components ofwellness from the Wheel of Wellness, namely 1) creativity and problem solving, 2)control feeling, 3) coping and emotional awareness, 4) senseof humour, 5) occupation,6) spare time, 7) stress management, 8) feeling of deserving, 9) realistic belief, 10)friendship, 11) love, 12) spirituality, 13) self care, 14) gender identity, 15) culturalidentity, 16) nutrition, dan 17) exercise, elaborated in the statements. In the WellnessEvaluation of Lifestyle (WEL) inventory in bahasa Indonesia there are 123 statementsrelated to wellness and 6 additional questions. The validity testing in the developmentof WEL inventory uses an expert judgement and the reliability of the inventory whichis 0.939 uses alpha cronbach 0.70 so the inventory can be used as a tool to identify thestudents’ wellness as the basis for the guidance and counseling service.